The effect of anterior cruciate ligament reconstruction and RAMP lesion repair on psychological status - Dansuk, Emre; Kemah, Bahattin; Polat, Gökhan; Erdil, Mehmet Emin (Springer Nature, 2023)
Background: There are few studies examining anterior cruciate ligament reconstruction (ACLR) and RAMP lesion repair. However, no studies have investigated the level of functional performance and psychological state after ACLR and all-inside RAMP lesion repair. Hypothesis/Purpose: The aim of this study is to determine the effect of ACLR and RAMP lesion repair on psychological status. ACLR and meniscal RAMP lesion repair were hypothesized to be associated with better psychological outcomes. Study Design: This is a cohort study. Methods: Patients who underwent ACLR with semitendinosus and gracilis autografts by a single surgeon were determined retrospectively. Fifteen patients who underwent ACLR and all-inside meniscus RAMP lesion repair (ACLR-RR) and 15 patients who underwent isolated ACLR were compared. Patients were evaluated by a physiotherapist at least 9 months after surgery. The primary outcome measure was anterior cruciate ligament-return to sports after injury (ACL-RSI), and the psychological status of the patients was examined. Secondary outcomes were visual analog scale (VAS), Tegner activity score, Lysholm knee score, single hop tests, and limb symmetry index (LSI). While pain intensity at rest and during movement was evaluated with VAS, functional performance level was evaluated with the Tegner activity score, the Lysholm knee score, single hop tests, and limb symmetry index (LSI). Results: A significant difference was found in the ACL-RSI values in the ACLR-RR group compared to the isolated ACLR group (p = 0.02). The results of the groups in VAS scores at rest and during movement, Tegner activity levels, and Lysholm knee scores, in the intact and operated leg single hop tests (single leg hop, cross hop, triple hop, and six-meter hop test), and the LSI values in the single leg hop tests showed no significant difference. Conclusions: This study revealed different psychological outcomes and similar functional levels for ACLR and all-inside meniscus RAMP repair compared with isolated ACLR. It was observed that the psychological status of patients with RAMP lesions should also be evaluated.
Keywords: ACL-RSI; ACLR; Hop Test; LSI; Meniscus; RAMP Lesion